Stilobezzia (Acanthohelea) curvistyla (Diptera: Ceratopogonidae), new association of sexes and redescription of male - Cazorla, Carla Gisela (2015)
Study of the type material, new specimens of Stilobezzia (Acanthohelea) curvistyla and recently collected Stilobezzia (A.) megatheca showed an erroneous association of sexes in both species. The female allotype of S. (A.) megatheca belongs to Stilobezzia (A.) curvistyla. The right association of sexes is provided, the male of S. (A.) curvistyla is redescribed, the species diagnosis is expanded and its geographic distribution is extended.